The Level of Maternal Knowledge and the Incidence of Ascariasis in School-Age Children - Latuheru, Friska (Omni Nursing Journal, 2024)
Background: Ascariasis disease occurs most often in school-age children. This is because school-age children often come into contact with the soil. School-age children are also the highest group infected with worms which are transmitted through the soil. Many cases of worms are found in the ascariasis worm group. Objective: The purpose of the study was to determine the relationship between the level of maternal knowledge and the incidence of ascariasis in school-age children in Ambon. Methods: This type of research was quantitative research with a cross-sectional approach. The sample size in this study was 75 respondents which was collected with total sampling technique. Th analysis test employed the Chi-square test. Results: This study found that the mothers' level of knowledge about ascariasis was in low category, which was 61 (81.3%) respondents, and most school-age children suffer from ascariasis infection, amounting 59 (78.7%) respondents. Furthermore, the mother's level of knowledge had a significant relationship with ascariasis infection with a p-value of 0.199 (>0.05), indicating that there was no relationship between the mother's knowledge level and the incidence of ascariasis infection. Conclusion: There is no relationship between maternal knowledge and the incidence of ascariasis infection.